Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. Role of strategic management in developing administrative competence of employees in Islamic banks in Tulkarm GovernorateMahmoud Hasan Hejazi2. The Impact of High-Performance Work Systems on Confrontation Competitive Challenges and The Role of Managerial Control as Moderating Variable in The Banking System at Dongola Locality in The Northern State of SudanMashair Hussien Khalifa Ali, Mahmoud AbdelMoati Hashem AbdelHamid3. The impact of non-oil economic determinants on Saudi economic growthAbu Al-Qasim Abbas Mohammed4. The effectiveness of the mechanisms for implementing the rules of international humanitarian law in PalestineMuamar Ali Orabi Nakhlah5. The Impact of Macroeconomic Policies on Foreign Direct Investment in Sudan (1990-2020)Ebtihaj Hashim Mohammad Algzoli6. Withdrawal Arguments and Their Applications in Iraqi Personal Status CourtsNadia Ali Hassan7. Humanitarian and Weapons of Mass Destruction International Humanitarian LawTahani Ahmed Ali
Keywords: Journal of Economic, Administrative and Legal Sciences